Cavity-control of interlayer excitons in van der Waals heterostructures - Michael Förg (Nature Portfolio, 2019)
Cavity-enhanced light-matter interaction in the weak-coupling regime is known to result in Purcell enhancement. Here the authors demonstrate Purcell enhancement in the photoluminescence of vertical MoSe2-WSe2 heterostructures coupled to a micro-cavity and determine the light-matter coupling strength for interlayer excitons.